Consistency test of precipitating ice cloud retrieval properties obtained from the observations of different instruments operating at Dome C (Antarctica) - G. Di Natale; D. D. Turner; G. Bianchini; M. Del Guasta; L. Palchetti; A. Bracci; L. Baldini; T. Maestri; W. Cossich; M. Martinazzo; L. Facheris (Atmospheric Measurement Techniques, 2022)
Selected case studies of precipitating ice clouds at Dome C (Antarctic Plateau) were used to test a new approach for the estimation of ice cloud reflectivity at 24 GHz (12.37 mm wavelength) using ground-based far infrared spectral measurements from the REFIR-PAD Fourier transform spectroradiometer and backscattering/depolarization lidar profiles. The resulting reflectivity was evaluated with the direct reflectivity measurements provided by a co-located micro rain radar (MRR) operating at 24 GHz, that was able to detect falling crystals with large particle size, typically above 600 µ m. To obtain the 24 GHz reflectivity, we used the particle effective diameter and the cloud optical depth retrieved from the far infrared spectral radiances provided by REFIR-PAD and the tropospheric co-located backscattering lidar to calculate the modal radius and the intercept of the particle size distribution. These parameters spanned in the wide ranges between 570–2400 µ m and 10 −2 – 10 4 cm −5 , respectively. The retrieved effective sizes and optical depths mostly varied in the ranges 70–250 µ m and 0.1–5, respectively. From these parameters, the theoretical reflectivity at 24 GHz was obtained by integrating the size distribution over different cross sections for various habit crystals provided by Eriksson et al. ( 2018 ) databases. From the comparison with the radar reflectivity measurements, we found that the hexagonal column-like habits, the columnar crystal aggregates, and the 5/6 <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="20pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="023af0f8880475ce1a583f0c7c2ff620"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-15-7235-2022-ie00001.svg" width="20pt" height="14pt" ...